Fast Gate Drive for SiC-JFET using a Conventional Driver for MOSFETs and Additional Protections - Piepenbreier, Bernhard; et al. (The 30th Annual Conference of the IEEE Industrial Electronics Society, 2004)
A new gate drive for SiC-JFET (Silicon Carbide Junction Field Effect Transistor) is developed and tested on a half-bridge. For the realization of a fast gate drive which offers full protection for the SiC-JFET, a gate drive concept is firstly chosen. The gate drive unit has an output stage made for MOSFETs, a new kind of fast signal isolator, short circuit protection and overvoltage protection. © 2004 IEEE.
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.LEEAS.fastga